2009
DOI: 10.1142/s0217984909019090
|View full text |Cite
|
Sign up to set email alerts
|

ULTRATHIN Al FILM ON THE W(100) SURFACE

Abstract: We have investigated Al adsorption on the W(100) surface using LEED and low energy Ion Scattering Spectroscopy (ISS). We observe a p(2 × 1) double domain LEED image for the 1.0 ML Al/W(100) surface at annealing temperature 850 • C. We also measured the Al adsorption site at the Al/W(100) -p(2 × 1) surface using ISS. It is found that Al atoms adsorbed at 0.7 ± 0.1Å aside from the center of the bridge sites with a zigzag structure -one atom adsorbs at the right-hand side and next atom at the left-hand side along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…6 In this study, we focus on the characterization of field emission ͑FE͒ measured in a diode, which is placed in a high-vacuum chamber. Usually, field emission is measured with a flat cathode and anode; since such a diode yields a uniform field, it enables a direct conversion of the applied voltage difference V into the field strength E through the equation E = V / d, where d is the distance between the anode and the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…6 In this study, we focus on the characterization of field emission ͑FE͒ measured in a diode, which is placed in a high-vacuum chamber. Usually, field emission is measured with a flat cathode and anode; since such a diode yields a uniform field, it enables a direct conversion of the applied voltage difference V into the field strength E through the equation E = V / d, where d is the distance between the anode and the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recently, carbon nanomaterials such as nanometer-sized crystalline diamond ͑nanodiamond͒, carbon nanotube, carbon nanofiber, and carbon nanowall ͑CNW͒ have been intensively investigated, the results of which have shown that as an excellent electron emitter, they should have large aspect ratio, low-threshold voltage, higher emission current density, and stable emission. [1][2][3] Recently, carbon nanomaterials such as nanometer-sized crystalline diamond ͑nanodiamond͒, carbon nanotube, carbon nanofiber, and carbon nanowall ͑CNW͒ have been intensively investigated, the results of which have shown that as an excellent electron emitter, they should have large aspect ratio, low-threshold voltage, higher emission current density, and stable emission.…”
Section: Introductionmentioning
confidence: 99%
“…8 Nishimura et al have reported that a high quality CNWs with an emission current density of 1 mA/ cm 2 at an electric field of 1.5 V / m have been fabricated by means of plasma-enhanced chemical vapor deposition ͑CVD͒ method. 3 Yue et al have demonstrated that medical diagnostic x-ray radiation can be generated using a carbon nanotube based field emission cathode. Choi et al have fabricated a fully sealed field-emission display of 4.5 in.…”
Section: Introductionmentioning
confidence: 99%
“…Patterning technique mainly includes catalyst growth by chemical vapor deposition 5,6 ͑CVD͒ and screen-printing method. 4,7 Various CNT slurries for screen printing have been reported, which are usually formed by mixing CNTs with organic vehicles and in some cases, metal particles or oxide conductive powders. Up to now, Samsung, ISE, and others have reported their FED prototypes based on the printed CNT emitters.…”
Section: Introductionmentioning
confidence: 99%